Effects of salinity and nitrogen supply on the quality and health‐related compounds of strawberry fruits (Fragaria × ananassa cv. Primoris). (8th January 2015) - Cardeñosa, Vanessa; Medrano, Evangelina; Lorenzo, Pilar; Sánchez‐Guerrero, Maria Cruz; Cuevas, Francisco; Pradas, Inmaculada; Moreno‐Rojas, José M
Abstract BACKGROUND Different nitrogen inputs and/or development under adverse water conditions (water stress/low quality and/or high salinity/electrical conductivity), such as those prevailing in Almeria (Mediterranean coast, south‐east Spain), may affect overall fruit and vegetable quality. This study evaluated the influence of salinity and nitrogen reduction in hydroponic nutrient solution on strawberry fruit quality and nutritional compounds (Fragaria × ananassa Duch., cv. Primoris). RESULTS Strawberries obtained under salinity treatments recorded the highest values for soluble solids content (SSC; all samplings); fruit taste was thus enhanced. Additionally, salinity improved fruit nutritional value, with higher contents of antioxidants compounds (first sampling). During first and second samplings, strawberries grown under N reduction and non‐saline conditions showed higher values for firmness compared to fruits developed under other treatments. Regarding health‐related compounds, few differences were found except for total polyphenols concentration and antioxidant activity for the first sampling, where strawberries grown under saline treatments obtained the highest values for both parameters. CONCLUSION The use of low‐quality waters, such as those found in Almeria (salinity, N9S and N5S) and low nitrogen inputs (N5, avoid environmental impact) for strawberry cultivation does not exert a negative impact on overall quality. Positive differences could be found in SSC, firmness and health‐related compounds when compared against the control treatment (N9). © 2014 Society of Chemical Industry